2006
DOI: 10.1038/sj.emboj.7601091
|View full text |Cite
|
Sign up to set email alerts
|

The molecular chaperone Hsp90 delivers precursor proteins to the chloroplast import receptor Toc64

Abstract: Precursor protein targeting toward organellar surfaces is assisted by different cytosolic chaperones. We demonstrate that the chloroplast protein translocon subunit Toc64 is the docking site for Hsp90 affiliated preproteins. Thereby, Hsp90 is recognised by the clamp type TPR domain of Toc64. The subsequent transfer of the preprotein from Toc64 to the major receptor of the Toc complex, namely Toc34, is affinity driven and nucleotide dependent. We propose that Toc64 acts as an initial docking site for Hsp90 asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(212 citation statements)
references
References 29 publications
3
206
2
1
Order By: Relevance
“…Cytosolic Hsp90 has been shown to participate in the posttranslational targeting of preproteins to the TOC-TIC and translocase of the outer membrane-translocase of the inner membrane (TOM-TIM) import machinery of chloroplasts and mitochondria, respectively (30,40). It was recently reported that cytosolic Hsp90 participates in translocation of antigen across the endosomal membrane into the cytosol in mammalian cells and also in dislocation of the cholera toxin A1 subunit from the ER into the cytosol (41,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytosolic Hsp90 has been shown to participate in the posttranslational targeting of preproteins to the TOC-TIC and translocase of the outer membrane-translocase of the inner membrane (TOM-TIM) import machinery of chloroplasts and mitochondria, respectively (30,40). It was recently reported that cytosolic Hsp90 participates in translocation of antigen across the endosomal membrane into the cytosol in mammalian cells and also in dislocation of the cholera toxin A1 subunit from the ER into the cytosol (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have implicated cytosolic Hsp90 in the targeting of preproteins to the TOC translocon (30), and the use of urea-denatured recombinant pre-SSU-3xFLAG eliminated the possibility that the effect on import was due to inhibition of cytosolic Hsp90 present in the reticulocyte lysate of in vitro translated preproteins (31). Three general stages of import have previously been defined (2,3,(21)(22)(23)(24)(25): energy-independent binding to the TOC receptors, early import intermediates spanning both TOC and TIC translocons formed in the presence of 0.1 mM ATP/GTP, and late import intermediates captured in the presence of high concentrations of ATP (>1 mM) that are fully translocated across the TOC translocon and remain engaged with the TIC complex.…”
Section: Dsp (mentioning
confidence: 99%
“…Although we do not know whether these differences are significant, it is perhaps germane that the substrate for the Table 2 experiments was produced in a wheat germ translation medium, which has been reported to contain additional factors such as 14-3-3 proteins and molecular chaperones (42,47) that can stimulate protein import. Although additional experiments are required to explore this point further, our data are consistent with the view that these factors might serve in some way to increase the efficiency of energy utilization during the import process.…”
Section: Discussionmentioning
confidence: 99%
“…This system yields relatively high amounts of soluble precursor, obviating the need for urea denaturation required of our bacterially expressed precursors before the import experiments. Additionally, precursors synthesized in this manner are added to the import reactions along with chaperones and other elements of the wheat germ translation mix that have been reported to be active in chloroplast import experiments (42). The radiolabeled precursor used in these experiments was GFP preceded by a stromal targeting signal comprising the prSSU transit peptide followed by 22 amino acids of the mature protein (tp22-GFP, Materials and Methods).…”
Section: Effect Of Inhibitors On Intrinsic Background Atpase Activitymentioning
confidence: 99%
“…In vitro cross-linking and co-immune precipitation experiments with antibodies against Toc64 revealed (Sohrt and Soll , 2000 ;Becker et al , 2004b ). It was later revealed that Toc64 only transiently associates with the TOC core complex (Schleiff et al , 2003b ) and functions in providing a docking site for Hsp90-affiliated preproteins via its TPR domain (Qbadou et al , 2006 ), indicating a function in post-translational protein translocation across the chloroplast outer envelopes. TPR domaincontaining proteins, which are found in all organisms in cellular compartments are known to contribute to posttranslational protein import by the interaction with cytosolic chaperones (Feldheim and Schekman , 1994 ;Young et al , 2003 ;Schlegel et al , 2007 ).…”
Section: The Molecular Framework Of the Toc Complexmentioning
confidence: 99%